(untitled) (International Journal of Irrigation and Water Management, 2020)
A field experiment was conducted at Indian Agricultural Research Institute, New Delhi during the crop season of 2007 to 2008 and 2008 to 2009 to study the effect of irrigation and sulphur on yield and water use efficiency of Indian mustard (Brassica juncea var. PusaJagannath). The experiment was carried out in split plot design with three replications. The treatments consisted of three levels of irrigation in the main plots [no irrigation, one irrigation at 45 days after sowing (DAS), and two irrigations at 45 DAS and 90 DAS] and four levels of sulphur in sub-plots (0, 15, 30, and 45 kg S/ha). The results showed that in both years of experimentation, application of two irrigations significantly increased the India mustard yield as indicated by dry matter accumulation, seed production, biological/biomass yield, and harvest index, in comparison to no irrigation. Also, the application of two irrigations, been on par with one irrigation, significantly enhanced seed and biological yield to 20.6 and 78.0 q/ha respectively in the first year, and 22.9 and 86.7 q/ha respectively in the second year, and the highest harvest index was obtained from the application of two irrigations in both years of the study. Water use efficiency as indicated by seasonal consumptive water use increased progressively with the increasing number of irrigations. Also, the amount of soil moisture extraction by the crop from upper layers increased and those from lower depth decreased with increase in the level of irrigation (from no irrigation to two irrigations) in both years of the study. Application of two irrigations to mustard gave higher net (yield) return and benefit-cost (B: C ratio) over one irrigation, which in turn, gave higher net benefit-cost return and B: C ratio than no irrigation. The increasing levels of sulphur application increased Indian mustard dry matter accumulation, seed and biological yield and harvest index. Seasonal consumptive water use by the crop and water use efficiency increased progressively with the increase level of sulphur application up to 45 kg S/ha . Quantity of soil moisture extraction from deeper layer increased with increase in the levels of sulphur application.